Contextualising Darwin’s theory of evolution in the Yorùbá human concept (2019)
This paper discusses African cosmology as seen in the indigenous religion of the Yoruba. The focus of this paper is creating a framework of how the theory of evolution can enhance further understanding of some Yoruba beliefs, chiefly, its concept of human. This is done by tracing the history of the theory of Evolution. This is necessary because Charles Darwin must have been influenced by the works of some scientists before him. Several arguments that humans descended from the Apes were also discussed in this paper. These are premised on the implication of such notion on world religions which suggest creationism notably that of a perfect human being which is at odds with the conclusion of evolution. This paper discusses also the Yoruba concept of human, a notion that is clearly different from the western one. The relationship between human being and nature in Yoruba understanding and its link to the theory of evolution forms a major fulcrum in this research. This paper concludes that Olódùmarè the creator endows humans with enormous power that can be used at will transforming to suit the prevailing situation, thereby making room for the theory of evolution.